Waist-to-calf circumstance ratio and cognitive function among Chinese older adults: Mediating roles of physical performance and social activity - Cao, Xia; Yang, Binfang; Zhou, Jiansong (Frontiers in Aging Neuroscience, 2023)
Background In light of the potentially detrimental effects of central fat and decreased muscle mass on cognitive function, it would be beneficial to learn more about the mediating mechanisms underpinning the association between the two. The purpose of this study is to determine the association between waist-to-calf circumstance ratio (WCR) and cognitive function, as well as to investigate whether physical performance and social activity mediate the relationship between WCR and cognitive function among older Chinese adults. Methods An analysis of 9,652 older Chinese adults was conducted during the 2018 wave of the Chinese Longitudinal Health Longevity Survey (CLHLS). The Mini-Mental State Examination (MMSE) and a self-reported scale were used to measure cognitive function, physical performance, and social activity, respectively. Multiple linear regression and mediation analyses were conducted. Results The findings suggest that a high WCR had a significant negative association with cognitive function (B = −0.535, 95% CI: −0.754, −0.317). Mediation analysis revealed that a high WCR influenced old adults' cognitive function in three ways: first, through the partial mediating effect of physical performance (B = −0.270; 95% CI: −0.340, −0.203); second, through the partial mediating effect of social activity (B = −0.035; 95% CI: −0.055, −0.017); and third, through the serial mediating effects of physical performance and social activity (B = −0.021, 95% CI: −0.029, −0.015). Conclusion The study results suggest the adverse impact of a high WCR on older adults' cognitive function, and the possible mechanisms of physical performance and social activity by which the association takes place. Multidimensional health and social interventions aimed at improving physical, social, and cognitive functioning among older adults with sarcopenic obesity are recommended.